Hak Berserikat dan Berkumpul Menurut UUD Pasal 28E Ayat 3 dan Pasal 21 Ayat 1 DUHAM; Tinjauan Aktivitas Ekonomi Islam - Hafid, Numan Sofari; Arifin, Tajul; Fauzia, Ine (Al-Muamalat Jurnal Hukum dan Ekonomi Syariah, 2025)
Ideally, the right to associate and assemble, as guaranteed in Article 28E Paragraph 3 of the 1945 Constitution of Indonesia and Article 21 Paragraph 1 of the Universal Declaration of Human Rights (UDHR), provides freedom for individuals and groups to participate in social, political, and economic life. However, in reality, the implementation of this freedom still faces challenges, especially in the context of Islamic economics in Indonesia, where existing regulations sometimes limit the development of this sector. The aim of this research is to analyze the role of the right to associate and assemble in strengthening Islamic economic activities in Indonesia. This study uses a normative legal approach with qualitative analysis, focusing on secondary data from relevant literature and legal documents. The results of the study indicate that the right to associate and assemble plays a crucial role in strengthening Islamic economics. This freedom allows the formation of Islamic-based economic organizations that support the principles of justice and transparency. The implementation of this right, although hindered by several regulations that are less supportive, still provides a strong foundation for society to collaborate in the development of a more inclusive and just economy.